1987
DOI: 10.1172/jci113060
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of thrombocytopenia in chronic autoimmune thrombocytopenic purpura. Evidence of both impaired platelet production and increased platelet clearance.

Abstract: Mechanisms of thrombocytopenia were studied in 38 patients with mild to moderately severe chronic autoimmune thrombocytopenia (AITP). 5"Cr and "'In-labeled autologous platelet turnover studies and in vitro analysis of committed megakaryocyte progenitors (CFU-Meg) were used as independent measures of platelet production. Autologous "'In-labeled platelet localization studies were performed to assess platelet clearance.Although there was no increase in the frequency of marrow CFUMeg, a specific increase in the CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
217
1
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(222 citation statements)
references
References 47 publications
1
217
1
3
Order By: Relevance
“…However, autologous platelet survival studies in the 1980s, showing that most ITP patients had normal or decreased platelet turnover, suggested that platelet production in chronic ITP may also be impaired. [3][4][5][6] This hypothesis is supported by early morphologic studies of ITP bone marrow showing normal or increased numbers of megakaryocytes with a shift to younger forms that lacked evidence of cytoplasmic granularity or platelet formation and manifested degenerative changes in the nucleus and cytoplasm. 13,14 Subsequent studies, using electron microscopy, showed 50% to 75% of ITP megakaryocytes had extensive damage consisting primarily of abnormalities of the demarcation membrane system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, autologous platelet survival studies in the 1980s, showing that most ITP patients had normal or decreased platelet turnover, suggested that platelet production in chronic ITP may also be impaired. [3][4][5][6] This hypothesis is supported by early morphologic studies of ITP bone marrow showing normal or increased numbers of megakaryocytes with a shift to younger forms that lacked evidence of cytoplasmic granularity or platelet formation and manifested degenerative changes in the nucleus and cytoplasm. 13,14 Subsequent studies, using electron microscopy, showed 50% to 75% of ITP megakaryocytes had extensive damage consisting primarily of abnormalities of the demarcation membrane system.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6] Because megakaryocytes express GPIIb-IIIa and GPIb-IX on their surfaces during maturation 7 and because most ITP autoantibodies react with one or both of these glycoprotein complexes, 8,9 it follows that autoantibody binding to megakaryocytes could interfere with platelet production and release from the bone marrow either by causing intramedullary megakaryocyte or platelet destruction or by interfering with megakaryocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, platelet kinetic studies have identified large subgroups of ITP patients with a decreased or normal platelet turnover. 40,41 Figure 2 The ultrastructure of megakaryocytes. ITP megakaryocyte showing features of apoptosis (a; Â 5000) and apoptosis-like cell death (paraapoptosis) (b; Â 7000).…”
Section: Is Platelet Production Impaired In Itp?mentioning
confidence: 99%
“…In autoimmune hemolytic anemia, the compensatory reaction is much more pronounced, except when circulating antibodies are directed to normoblasts [31]. Previous studies have shown that, in the majority of ITP patients, the PPR is either reduced or normal [28,30,[32][33][34][35][36]. Additional support for a suppressed platelet production in ITP comes from in vitro studies showing that megakaryocyte production and maturation can be inhibited by antiplatelet antibodies [1,2,37].…”
Section: Discussionmentioning
confidence: 99%